1983
DOI: 10.1099/00221287-129-4-965
|View full text |Cite
|
Sign up to set email alerts
|

An Enzymic Analysis of NADPH Production and Consumption in Candida utilis

Abstract: Candida utilis CBS 621 was grown in chemostat cultures at D = 0.1 h-' on glucose, xylose, gluconate, acetate, or ethanol as the growth-limiting substrate with ammonia or nitrate as the nitrogen source and analysed for NADPH-producing and NADPH-consuming enzyme activities.Nitrate and nitrite reductases were strictly NADPH-dependent. For all carbon sources, growth with nitrate resulted in elevated levels of HMP pathway enzymes. NADP+-linked isocitrate dehydrogenase did not vary significantly with the NADPH requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
119
0
1

Year Published

1988
1988
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 7 publications
(7 reference statements)
1
119
0
1
Order By: Relevance
“…A second solution to this redox imbalance would be to convert NADH into NADPH with a transhydrogenase. However, no such enzymes have been discovered in yeasts (Blank et al 2005;Bruinenberg et al 1983b) and introduction of a heterologous transhydrogenase in S. cerevisiae has demonstrated that in vivo conditions favour NADPH production (Nissen et al 2001).…”
Section: Xylose Fermentationmentioning
confidence: 99%
“…A second solution to this redox imbalance would be to convert NADH into NADPH with a transhydrogenase. However, no such enzymes have been discovered in yeasts (Blank et al 2005;Bruinenberg et al 1983b) and introduction of a heterologous transhydrogenase in S. cerevisiae has demonstrated that in vivo conditions favour NADPH production (Nissen et al 2001).…”
Section: Xylose Fermentationmentioning
confidence: 99%
“…Under anaerobic conditions, it can be assumed that all lipid in biomass is formed from oleic acid in the medium. For the lipid composition under aerobic conditions, a simplification has been made according to Bruinenberg et al (1983), in that all lipid is assumed to be in the form of triglycerides with three long-chain neutral fatty acids; i.e. : palmitoleic acid 13.7; linoleic acid 5.5; oleic acid 8.2; and glycerol 9 mmol-100g cells -I.…”
Section: Calculations Of Theoretical Energy Requirements For Biomass mentioning
confidence: 99%
“…The yield can then be calculated. The reducing equivalents required for ATP production originate from two sources: Firstly, a net production of NADH and/or FADH is obtained in the overall anabolic reactions of most carbon sources commonly employed for yeast growth (Bruinenberg et al 1983;Gommers et al 1988). The assimilation equation for the production of 100 g biomass of S. cerevisiae 8066, including glucose required for the formation of NADPH (as calculated according to Verduyn et al 1990a), is given by: 55 775 C6H120 6 + 540 NH3---~ 1000 C3,75H6.602.18N0.54 (100 g biomass) + 902 CO: + 1426 NADH + 735 H20…”
Section: Calculation Of P/o-ratios For Growth On Glucosementioning
confidence: 99%
See 1 more Smart Citation
“…The pH was controlled by automatic addition of 2 M-KOH. The medium was prepared according to Bruinenberg et al (1983). The organism was grown under glucose limitation (S, 5 g 1-l) with ammonium as the nitrogen source, or under ammonium limitation ( S , 0-4 g 1-l) with glucose as the carbon source (S, 5 g l-l), or under glutamate limitation (carbon limitation without ammonium) ( S , 5 g P I ) .…”
Section: E T H O D Smentioning
confidence: 99%